The Policy of Ageing in Scandinavian Countries – Good Practices - Zapędowska-Kling, Kaja (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The consequences of demographic changes and aging populations are experienced by the whole Europe. Recently, the majority of the European Union Member States have decided to raise the retirement age. In the light of the world economic crisis and the instability of the Eurozone, the Scandinavian countries remain a mainstay of stabilization and social dialogue. From the perspective of social policy, Scandinavia offers a collection of good practices. Financed by the state, extensive system of home care, services tailored to customers' individual needs, innovation and application of new technologies in social services sector, implementation of effective legislative instruments to encourage seniors' social and professional activity are only some of the features of the Nordic model of the policy of ageing.